Pengaruh Rebusan Daun Pegagan Terhadap Tekanan Darah Lansia di Tersangede Salam Kabupaten Magelang - Nurrahmanto, Fajar; Handayani, Estrin; Priyanto, Sigit (Borobudur Nursing Review, 2021)
Background:: Hypertension is a condition in which a person experiences an increase in blood pressure above normal which results in increased morbidity and mortality. Blood pressure that is still considered normal is less than 150/90 mmHg, whereas if it is more than 160/90 mmHg it is considered hypertension in the elderly. Efforts are made to lower blood pressure using gotu kola leaf decoction. Destination: To determine the effect of gotu kola leaf decoction on lowering blood pressure. Method: This type of research is Quasi Experiment using two group pretest and posttest design with control group design with a sample of 44 respondents. The data were processed using the Wilcoxon test and the Mann Whitney test. The Result: Based on the Mann Whitney test on blood pressure, the Asym Sig. (2-tailed) is 0.000 where the p value <0.05, which means that. Conclusion: It was concluded that there was an effect of gotu kola leaf decoction on the decrease in blood pressure in the elderly in Tersan Gede Village, Salam District, Magelang Regency.